Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pendapatan Pengusaha di Sentra Industri Alas Kaki Wedoro Waru Kabupaten Sidoarjo - Renny Suci Oktami; Sugeng Widodo (Economie: Jurnal Ilmu Ekonomi, 2020)
The purpose of this study is to determine the effect of capital, labor, working hours, and prices on the level of income of entrepreneurs in Wedoro Waru footwear industry center in Sidoarjo Regency. This research uses a quantitative research approach. This study has a population of 79 respondents with sample determination using the Slovin formula, so the sample in this study amounted to 66 respondents of entrepreneurs in Wedoro Waru footwear industry center in Sidoarjo Regency. The results of multiple linear regression analysis obtained the results that capital, labor, working hours affect the level of income of entrepreneurs in Wedoro Waru footwear industry center in Sidoarjo Regency and prices do not affect the income level of entrepreneurs in Wedoro Waru footwear industry center in Sidoarjo Regency.